Challenges encountered by children with disabilities accessing child sexual abuse interventions in Zimbabwe - Muridzo, Noel G.; Chikadzi, Victor; Kaseke, Edwell (Springer Nature, 2020)
This article brings to the fore the challenges encountered by child sexual abuse survivors with disabilities accessing existing child sexual abuse medical, legal, social and psychological interventions in Zimbabwe. Using qualitative data from a multiple-case study research project, this article argues that child sexual abuse survivors with prelingual deafness, physical, mental, hearing and visual disabilities experience social and physical barriers, communication challenges and lack of participation in the Victim Friendly System. The authors further argue that impairments have tended to militate against children with disabilities’ capacity to access existing services. The Victim Friendly System is a confluence of medical, legal, psychological and social services for child sexual abuse survivors. To enable capacity to access existing services by child sexual abuse survivors with disabilities, the training of professionals in sign language and the use of braille is recommended. The paper also calls for the adoption and implementation of disability-sensitive policies.